The Influence of Cell Temperature and Installation Angle on Photovoltaic Energy Generation in Iran - Ali Ghayedhosseini; Hossein Yousefi; Amirhossein Fathi; Hassan Emad (Environmental Energy and Economic Research)
This study investigates the impact of cell temperature on the optimal installation and forecasting of photovoltaic (PV) power generation in Iran. Three scenarios are examined to quantify the effect of cell temperature on PV panel performance and installation angle: (1) ignoring temperature effects, (2) installing panels at the angle with maximum annual radiation, and (3) installing panels at the angle with maximum annual energy production. Optimal installation angles, annual solar energy radiation, and electricity production are evaluated at multiple locations throughout Iran. The results demonstrate that the optimal installation angle of PV panels does not significantly differ among the three scenarios. Cell temperature has some effect on panel performance, and the electricity generated by PV located in the areas of the sixth solar radiation decile is more than the areas of the country located in the tenth solar radiation decile. The estimated amount of solar radiation on the panel surface at the optimal angle in cities and settlements in Iran ranges from 1170 to 2517 kWh/m2.yr, while the corresponding electrical energy production ranges from 189.5 to 394.22 kWh/m2.yr.